Concepts in the Digital Inequality Literature: An Analysis of Foci and Distinctions (Third Sector Social Economic Review, 2026)
Inequality has long been a significant problem in many areas of social life. With the spread of digital technologies into every aspect of social life, these discussions have taken on a digital dimension. While early studies focused on digital inequality primarily in terms of individuals’ access to digital technologies, it has gradually become clearer that these technologies are structural systems that shape decision-making processes, the distribution of opportunities, and social hierarchies. This transformation directly affects not only individuals’ participation in social life but also their access to labor markets, working conditions, and the dynamics of corporate competition. While this development has expanded the digital inequality literature, the concept's broadening scope has blurred conceptual distinctions. In this context, concepts such as the digital divide, digital discrimination, algorithmic discrimination, algorithmic bias, and the digital red line are often used interchangeably in the digital inequality literature. This ambiguity between concepts makes it difficult to analytically distinguish between different dimensions of digital inequality, such as access, usage, algorithmic processes, and institutional regulations. This study aims to reveal which problem areas the aforementioned concepts correspond to and at which levels of digital inequality they are positioned. In this regard, a comparative conceptual analysis approach has been adopted; the definitions and discussions in the literature have been examined, and the contexts of use and distinctive focuses of the concepts have been analyzed.
Keywords: Digital Inequality; Digital Divide; Digital Discrimination; Algorithmic Discrimination and Bias; Digital Redlining